1987
DOI: 10.1002/anie.198705521
|View full text |Cite
|
Sign up to set email alerts
|

2,5‐Diazapentalenes

Abstract: each other is reduced. Indeed, a reduced sliding ability of the molecules, dependent on T,,, and thus an increase in intermolecular cross-linkage is demonstrated by the delayed increase in [?/Ii shown in Figure 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…Gompper and co-workers proposed a method consisting of heating the succinic acid diamide with N , N -dimethylbenzamide diethyl acetal ( 36 , Scheme 18 ). [ 24 ] Two products can be obtained by this reaction: DPP 2 (30% yield) and compound 37 , the latter of which can be quantitatively converted to DPP 2 by the action of potassium tert -butoxide (overall yield of DPP: ∼60%). The analogous reaction of succinic amide with tetramethylurea acetal 38 leads to the product 39 , which is a non-conjugated tautomer of DPP (Scheme 18 ).…”
Section: Other Methods Of Dpp Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Gompper and co-workers proposed a method consisting of heating the succinic acid diamide with N , N -dimethylbenzamide diethyl acetal ( 36 , Scheme 18 ). [ 24 ] Two products can be obtained by this reaction: DPP 2 (30% yield) and compound 37 , the latter of which can be quantitatively converted to DPP 2 by the action of potassium tert -butoxide (overall yield of DPP: ∼60%). The analogous reaction of succinic amide with tetramethylurea acetal 38 leads to the product 39 , which is a non-conjugated tautomer of DPP (Scheme 18 ).…”
Section: Other Methods Of Dpp Synthesismentioning
confidence: 99%
“…DPPs react with thiation reagents, such as phosphorus pentasulfi de (P 4 S 10 ) and Lawesson's reagent (LR), to give blue-green dithioketopyrrolopyrroles 62 with a good yield ( Scheme 27 ). [ 24,40 ] By this method, DPP 2 was converted to dithiolactam 62a , a compound existing in several polymorphic crystalline forms. The photophysical and electronic properties of these forms were thoroughly studied, mainly by Mizuguchi and co-workers.…”
Section: Modifi Cations Of Carbonyl Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another synthetic modification of the succinic acid principle was found by Closs and Gompper in the reaction of succindiamide with N,N-dimethylbenzamide diethyl acetal [7].…”
Section: Introductionmentioning
confidence: 99%
“…These heterocyclic compounds have been the object of several crystallographic studies and it was shown that the solidstate arrangement of DPP molecules occurs in parallel sheets. [6][7][8][9] The colour derives not only from the molecular structure, but also from the supramolecular order (p-p-interactions between the layer of molecules), since the colour in solid state differs from the colour in very dilute solutions. 10 The hydrogen bonding between neighbouring lactam-nitrogen and carbonyl-oxygen atoms is crucial for pigments in order to limit solubility.…”
Section: Introductionmentioning
confidence: 99%